Konflik Interorganizational System (IOIS) Pada Organisasi : Studi Kasus Pada Industri Outsourcing - Nugroho, Chrismantya Dwi Satriya (Journal Business Administration: Entrepreneurship and Creative Industry, 2023)
ABSTRACT: Adoption of IOIS often causes conflicts in both corporate and partner relationships, this is due to unequal interests, corporate culture and corporate resources. The outsourcing industry is faced with different business partner models, both in terms of business processes and resources, which is a challenge in IOIS integration. This study aims to determine the conflict in IOIS adoption in the outsourcing industry with the complexity of IOIS integration as well as identifying potential new conflicts in Interorganizational studies. The outsourcing industry, which is faced with different partner business models both in terms of business processes and resources, is a challenge in IOIS operations, especially in diverse organizational governance, create system support and information technology that can lead to bad IOIS adoption if there is no intensity of communication and agreement. This study is a case study research with a qualitative approach, which is a process of research and understanding to investigate a phenomenon and problem. It is known that the standard operating procedure (SOP) is considered to be difficult for partners and disrupts IOIS integration so that it can cause some alliances not to want to use IOIS services. However, from a technical point of view, the absence of an SOP will affect the quality of the data/input obtained, thereby affecting the resulting output. Differences in viewpoints and interests between CEOs and CIOs are at the root of a series of interlocking conflicts.